PROCESS-ORIENTED APPROACH TO ACCOUNTING COSTS AND CALCULATING THE COSTS OF PRODUCTION OF ENTERPRISES MANUFACTURING PRECAST REINFORCED CONCRETE STRUCTURES - OVOD, Larysa; VALKOVA, Nataliia; KORBUT, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Costs are one of the most important economic categories, and production costs are the main indicator of construction materials industry enterprises activity. In today’s difficult business conditions for Ukrainian enterprises, taking into account the specifics of the production process of companies producing prefabricated reinforced concrete structures, constant monitoring of production costs helps to maintain the profitability and competitiveness of these business entities. Therefore, the development of management tools and cost accounting using a process-oriented approach for enterprises producing building materials allows taking into account all the features of production processes influencing the size and behavior of costs. The purpose of the article is to reveal and improve the features of cost accounting and costing of products according to production processes at enterprises producing precast reinforced concrete structures. The article analyzes the main directions of classification of production processes at enterprises of the production of prefabricated reinforced concrete structures and its influence on the organization of accounting. The directions for grouping costs in production processes are detailed and attention is focused on its impact on accounting and control of the costs. This will affect the quality of management decisions and the main performance indicators of the enterprises under study. In the process of research, the main foreign methods of accounting for costs and calculating the cost of products in production processes, which are possible for use at enterprises of the production of precast reinforced concrete structures, were determined. It was found that the ABC-costing method is the most acceptable from the point of view of the technological process of manufacturing products of the studied enterprises. Its combination with the regulatory method of cost accounting and product costing will provide significant opportunities for strategic planning of production costs, will contribute to the accuracy of product costing, and will improve the process of management decision-making.